(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Flax is the multiple purpose crop cultivated in temperate region. Seeds of oil flax recently became important constituent for many industrial applications, such as pharmacy, medicine, food production etc. and have high prospective for use in Latvia. Understanding the underlying processes that limit seed yield in flax is major with respect to enhancing the breeding of flax for yield improvements. The aim of study was evaluated 29 flax varieties and lines (including 20 Latvian origins) plasticity of seed yield production in changeable environmental conditions. The experiment was carried out in the Agricultural Scientific Centre of Latgale on field trials over the period 2010-2013. The aim of this study was evaluated plasticity in changeable environmental conditions for 29 flax varieties and lines (including 20 Latvian origins). According to 4 years results was to establish the nature of relation between seed yield and hydrothermal coefficient (HTC), and seed yield and another yield components of flax. Apart from the changing conditions highest seed yield were produced from a varieties ‘Lirina’ (2.54 h -1t), high seed oil content from variety ‘Amon’ (53.03%). Positive and significant relationships were found between seed yield and HTC ‘T30-28-6-94’(r=+0.98*), ‘German Serenade’ (r=+0.95*) and ‘Scorpion’ (r =+0.95*).